INCREASING STUDENTS READING SKILL USING LITERATURE: CLASSROOM ACTION RESEARCH AT MAN 1 PROBOLINGGO - Syauqiah, Anggraini Sifaus; Tirmidi, Tirmidi; Supaidi, Agus (Jurnal Review Pendidikan dan Pengajaran, 2025)
The purpose of this study was to use literary works as a learning tool to improve the reading skills of students at MAN 1 Probolinggo. A two-cycle classroom action research (CAR) was used. The stages of planning, action, observation, and reflection were its components. The study involved twelve students studying language in grade XII, and the results showed a significant improvement in their reading skills. Although most students did not achieve the minimum passing grade of 75, almost all students exceeded the minimum passing grade on the subsequent test, and six of them received perfect scores. Literature-based learning also increased student engagement, interest, and appreciation for reading.